Coupling SOFCs to biomass gasification - The influence of phenol on cell degradation in simulated bio-syngas. Part I: Electrochemical analysis. (8th November 2018) - Geis, Michael; Herrmann, Stephan; Fendt, Sebastian; Jeong, Hyeondeok; Lenser, Christian; Menzler, Norbert H.; Spliethoff, Hartmut
Abstract: Feeding solid oxide fuel cells (SOFCs) with gas from biomass gasification is promising with regard to highly efficient power generation. But it is also intricate since biogenic contaminants are harmful to state-of-the-art anode materials. In this work the influence of phenol as a biogenic model contaminant on the performance of single solid oxide fuel cells was studied under realistic conditions. For this purpose Ni/YSZ anode supported cells were operated with simulated bio-syngas, applying an electrical load of 0.34 A/cm 2 . Over a duration of several hundreds of hours phenol was periodically added to the fuel gas. The tests showed that for the lowest concentration of phenol no accelerated degradation could be observed regarding cell potential and electrical impedance measurements, but disintegration of the Ni/YSZ support took place. Metal dusting of the anode support was found to be the most important mechanism of degradation. Highlights: 1, 5 g/Nm³ (360 ppm) of phenol cause disintegration of the anode substrate. Metal dusting is identified as degradation process. Incomplete reforming of phenol causes carbon deposition triggering metal dusting. The anode support is the critical part for stable long-term operation on bio-syngas. The recorded impedance data indicate carbon deposition in the anode layer.